GAMBARAN SUBJECTIVE WELL BEING SISWA SMA - Feby Hazimi; Nurfarhanah; Yarmis Syukur; Puji Gusri Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the problem that many students have low subjective well-being due to academic pressure and demands from their parents. One factor that causes low subjective well-being of students is the lack of social support from parents. This study aims to describe the level of life satisfaction of high school students, describe subjective well-being in high school students viewed from positive aspects, and describe subjective well-being in high school students viewed from negative affect aspects. The research method used in this study is quantitative using descriptive analysis techniques. The sample of this study was 292 students selected using proportional random sampling technique. The instrument used in this study was the subjective well-being instrument. The results of this study indicate that subjective well-being of students in South Solok High School is generally in the moderate category. Based on the results of the study, guidance and counseling teachers can provide information services, individual counseling services and group guidance to help students who experience problems with their subjective well-being, as well as topics that can be used are how to improve subjective well-being.